Perencanaan Tebal Perkerasan Lentur (Flexible Pavement) Dengan Metode Aashto, Jica Dan Bina Marga (MDP-2017) Pada Jalan Raya Sawunggaling, Kletek, Sidoarjo - saktiyan andre arko (AGREGAT, 2022)
Sawunggaling Road, Klethek, Sidoarjo Regency is an alternative road from Sukodono District to provincial highway. Every day the road is passed by heavy transport trucks from the industrial area to the city and motor vehicles that pass to go to work and travel. With high intensity and capacity, the highway is increasingly increasingly many points that experience asphalt damage, such as potholes, edge cracks, middle cracks, and basins.  The approval of the research planned the thick bending pavement on the road sawunggaling by considering 3 calculation methods, namely AASHTO, JICA and Bina Marga.In this research, the researcher conducted literature studies and data collection and collection. Data collection consisted of 2 types. First the primary data in the form of road dimension surveys, vehicle speed surveys and LHR data, the second secondary data in the form of regional factors, CBR data and thick pavement existing roads. Furthermore, the data was processed and analyzed using 3 methods, namely AASHTO, JICA and Bina Marga.From the results showed that each thick layer of new road bending pavement, namely from various segments, one of which was spelled out, namely: segment 1 in the AASHTO method value of layer D1 7.5 cm; D2 15 cm; D3 20 cm, in the JICA method the value of layer D1 10 cm; D2 15 cm; D3 20 cm, in the method of building marga the value of layer D1 7.5 cm; D2 15 cm; D3 20 cm. therefore, in the selection of the right and effective method of road planning in Indonesia, namely the Bina Marga method. It was hoped that this planning can provide a good analysis for damage to the Sawunggaling road. Keywords : Thick New Road Pavement, AASHTO, JICA, Bina Marga